RELASI BUDAYA ORGANISASI DAN POLITIK TERHADAP SUKSESI REFORMASI BIROKRASI - Rudi Salam Sinaga (PERSPEKTIF, 2012)
Bureaucratic reform requires the creation of good governance, namely the process of interaction between state institutions to the community derived from elements of civil society in order to perform the construction and establishment of good governance. In the practice to achieve Good Governance found "stagnation" due to the political culture of the organization and not show his support for a succession of bureaucratic reform. This study will look at organizational culture and political relations to the establishment of Good Governance in Indonesia. The method used is descriptive evaluative with the type of qualitative research. The results showed that organizational culture and politics play a major role in the"stagnant" succession of reforms would require strong leadership and visionary in order to oversee the achievement of a succession of bureaucratic reform in Indonesia.